Golf ball
The golf ball design with a natural rubber spherical core and a soft outer cover addresses the challenge of inconsistent spin and feel during approach shots, resulting in improved controllability and reduced rolling distance.
Patent Information
- Application Number
- JP2023172935
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing golf balls struggle to provide a consistent amount of spin during approach shots due to unstable impact points, leading to difficulty in controlling the rolling distance and feel.
A golf ball design featuring a spherical core made from a rubber composition with natural rubber, a co-crosslinking agent, and a crosslinking initiator, with a specific hardness distribution and a soft outermost layer cover to enhance feel and controllability.
The golf ball achieves a good hitting feel, reduced rolling distance, and improved controllability during approach shots, allowing for better control over the distance and spin.
Smart Images

Figure 2025063592000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a golf ball, and more particularly to a golf ball having a spherical core, an intermediate layer, and an outermost cover layer. [Background technology]
[0002] Conventionally, spherical cores made of various rubber materials have been proposed as the spherical cores of golf balls. For example, Patent Document 1 describes a driving range golf ball obtained by vulcanizing a composition containing 3 to 35 parts by weight of low-resilience rubber, 20 to 30 parts by weight of methacrylic acid, and 20 to 50 parts by weight of a metal compound capable of forming a metal salt with methacrylic acid, per 100 parts by weight of base rubber (see Patent Document 1 (Claim 1, page 3, upper left column, lines 11 to 17)).
[0003] Patent Document 2 describes a golf ball for use at driving ranges obtained from a composition containing 100 parts by weight of a base rubber, 3 to 35 parts by weight of 10 to 60 mol % epoxidized natural rubber, 20 to 35 parts by weight of methacrylic acid, and 20 to 50 parts by weight of zinc oxide (see Patent Document 2 (Claim 1, page 2, lower left column, line 4 to lower right column, line 2)). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 60-92780 [Patent Document 2] Japanese Patent Application Publication No. 61-71069 Summary of the Invention [Problem to be solved by the invention]
[0005] What is important in an approach shot is to stop the ball on the green and get it close to the pin, so the development of a golf ball with an increased amount of spin on an approach shot is being considered. However, the amount of spin varies depending on the variation in the impact point, and it is difficult for average golfers to control the amount of spin because the impact point is not stable. In addition, with a golf ball with an increased amount of spin, the amount of change in the amount of spin increases due to the variation in the impact point, and the amount of change in the distance at which the ball stops (the amount of roll) also increases, making it more difficult to adjust the flight distance. In approach shots, the feel of the shot is also important in order to get the right sense of distance, so it is preferable for the shot to have a soft feel.
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a golf ball which provides a good shot feeling on approach shots, a short rolling distance, and excellent controllability. [Means for solving the problem]
[0007] The golf ball of the present invention, which has been able to solve the above problems, has a spherical core, an intermediate layer covering the spherical core, and an outermost cover layer covering the intermediate layer, the spherical core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator, the base rubber containing natural rubber, and the spherical core has a center hardness (H0), a hardness at a radial distance of 2.5 mm from the center of the spherical core (H 2.5 ), and the hardness (H 5.0 ), and the hardness (H 7.5 ), and the hardness (H 10 ), and the hardness (H 12.5 ), and the hardness (H 15 ) and surface hardness (Hs), H0 <H 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15Satisfies the relationship of <Hs>, the core hardness (H0) of the spherical core is 60 or less in Shore C hardness, and the slab hardness of the intermediate layer composition forming the intermediate layer is greater than the slab hardness of the cover composition forming the outermost layer cover.
[0008] Since the golf ball of the present invention contains natural rubber as the base rubber of the rubber composition forming the spherical core, the launch angle at the approach shot becomes high, and the initial ball speed can be suppressed low. Further, by controlling the hardness distribution of the spherical core, the deformation of the spherical core occurs smoothly, and the hitting feeling of the approach shot becomes good. And in the golf ball of the present invention, since the hitting feeling at the approach shot is good and the initial ball speed is low, it becomes easy to control the rolling distance, and the controllability is improved.
Advantages of the Invention
[0009] According to the present invention, a golf ball having a good hitting feeling at the approach shot, a small rolling distance, and excellent controllability can be obtained.
Brief Description of the Drawings
[0010] [Figure 1] It is a partially cut-away cross-sectional view showing the golf ball according to the present invention.
Embodiments for Carrying Out the Invention
[0011] The golf ball of the present invention has a spherical core, an intermediate layer covering the spherical core, and an outermost layer cover covering the intermediate layer.
[0012] (Spherical Core) The spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator.
[0013] The base rubber contains natural rubber (NR). The natural rubber is produced by harvesting the latex (milky liquid) from a plant that produces natural rubber, by scratching the plant, and coagulating the rubber component contained in the latex. The natural rubber may be used alone or in combination of two or more types.
[0014] Examples of plants that produce natural rubber latex include Hevea brasiliensis and Hevea serowata of the Euphorbiaceae family, Rubber tree, Panagium, and Lagos of the Mulberry family, Gum arabicum, Tragacanth, Curculionidae, Zanzibar vine, Huntsumia elastica, and Urceola of the Fabaceae family, Guayule, and Rubber dandelion of the Asteraceae family, Gutta-percha, Balata, and Sapodilla of the Sapotaceae family, Morning glory of the Asclepiadaceae family, and Eucommia of the Eucommaceae family.
[0015] The natural rubber may be a CV grade in which the rubber viscosity is stabilized by adding a viscosity stabilizer or the like to the raw latex, or a non-CV grade in which the rubber viscosity is not stabilized. These may be used alone or in combination of two or more. Among these, a CV grade having a particularly stable viscosity is preferred. The natural rubber may be either SMR (standard Malaysian rubber) or SVR (standard Vietnam rubber).
[0016] The natural rubber is cis-1,4-polyisoprene, and either sheet rubber or block rubber can be used. Natural rubber also includes modified natural rubbers, such as epoxidized natural rubber, methacrylic acid modified natural rubber, halogen modified natural rubber, deproteinized natural rubber, maleic acid modified natural rubber, sulfonic acid modified natural rubber, and styrene modified natural rubber. Of these, it is preferable that the natural rubber does not contain epoxidized natural rubber.
[0017] The natural rubber is preferably Technical Specified Rubbers (TSR) or Ribbed Smoked Sheet (RSS). The natural rubber may contain a viscosity stabilizer.
[0018] The Mooney viscosity (ML 1+4 (100°C)) is preferably 30 or more, more preferably 35 or more, and even more preferably 40 or more, and is preferably 80 or less, more preferably 75 or less, and even more preferably 70 or less. In this specification, the Mooney viscosity (ML 1+4 (100°C) is the value measured in accordance with JIS K6300 (2013) using an L rotor with a preheating time of 1 minute, rotor rotation time of 4 minutes, and at 100°C.
[0019] The base rubber may contain only natural rubber, or may contain natural rubber and synthetic rubber. When the base rubber contains natural rubber and synthetic rubber, the content of natural rubber in 100% by mass of the base rubber is preferably at least 20% by mass, more preferably at least 30% by mass, even more preferably at least 40% by mass, and particularly preferably at least 70% by mass. If the content is 20% by mass or more, the controllability of the flight distance on approach shots is further improved.
[0020] Examples of the synthetic rubber include diene rubbers such as polybutadiene rubber (BR), polyisoprene rubber (IR), styrene polybutadiene rubber (SBR), chloroprene rubber (CR), butyl rubber (IIR), and acrylonitrile butadiene rubber (NBR); and non-diene rubbers such as ethylene propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), urethane rubber, silicone rubber, acrylic rubber, epichlorohydrin rubber, polysulfide rubber, fluororubber, and chlorosulfonated polyethylene rubber. These may be used alone or in combination of two or more.
[0021] The base rubber may contain a diene rubber as a synthetic rubber. In this case, the content of the diene rubber in 100% by mass of the base rubber is preferably at least 5% by mass, more preferably at least 10% by mass, and even more preferably at least 15% by mass, and is preferably at most 80% by mass, more preferably at most 70% by mass, and even more preferably at most 60% by mass.
[0022] The base rubber preferably contains polybutadiene rubber as a diene rubber. In particular, it is more preferable that the base rubber contains high-cis polybutadiene having cis-1,4-bonds in an amount of 40% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more. The content of high-cis polybutadiene in the diene rubber is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. It is also preferable that the diene rubber contains only high-cis polybutadiene rubber.
[0023] The high-cis polybutadiene preferably has a 1,2-vinyl bond content of 2.0% by mass or less, more preferably 1.7% by mass or less, and further preferably 1.5% by mass or less.
[0024] The high-cis polybutadiene is preferably one synthesized using a rare earth element catalyst. In particular, the use of a neodymium-based catalyst using a neodymium compound, which is a lanthanum series rare earth element compound, is preferred because it can produce a polybutadiene rubber having a high content of 1,4-cis bonds and a low content of 1,2-vinyl bonds with excellent polymerization activity.
[0025] The high cis polybutadiene preferably has a molecular weight distribution Mw / Mn (Mw: weight average molecular weight, Mn: number average molecular weight) of 2.0 or more, more preferably 2.2 or more, even more preferably 2.4 or more, and preferably 6.0 or less, more preferably 5.0 or less, even more preferably 4.0 or less. If the molecular weight distribution (Mw / Mn) of the high cis polybutadiene is within the above range, the workability is improved. The molecular weight distribution is measured by gel permeation chromatography (manufactured by Tosoh Corporation, "HLC-8120GPC") using a differential refractometer as a detector under the conditions of column: GMHHXL (manufactured by Tosoh Corporation), column temperature: 40°C, and mobile phase: tetrahydrofuran, and is calculated as a standard polystyrene equivalent value.
[0026] The Mooney viscosity (ML 1+4 (100° C.) is preferably 30 or more, more preferably 32 or more, and even more preferably 35 or more, and is preferably 140 or less, more preferably 120 or less, and even more preferably 100 or less.
[0027] The co-crosslinking agent has the effect of crosslinking rubber molecules by graft polymerization with the base rubber molecular chain. The co-crosslinking agent may be used alone or in combination of two or more. The co-crosslinking agent is preferably an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or a metal salt thereof. Examples of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms include acrylic acid, methacrylic acid, fumaric acid, maleic acid, and crotonic acid.
[0028] Examples of the metal constituting the metal salt of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms include monovalent metal ions such as sodium, potassium, and lithium; divalent metal ions such as magnesium, calcium, zinc, barium, and cadmium; trivalent metal ions such as aluminum; and other ions such as tin and zirconium. The metal components can be used alone or in combination of two or more. Among these, divalent metals such as magnesium, calcium, zinc, barium, and cadmium are preferred as the metal components. This is because the use of a divalent metal salt of an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms facilitates the formation of metal crosslinks between rubber molecules. In particular, zinc acrylate is preferred as the divalent metal salt because it increases the resilience of the resulting golf ball. The α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or its metal salt may be used alone or in combination of two or more.
[0029] The content of the co-crosslinking agent may be appropriately adjusted depending on the desired hardness of the spherical core. The content of the co-crosslinking agent is preferably 20 parts by mass or more, more preferably 23 parts by mass or more, and even more preferably 25 parts by mass or more, and is preferably 60 parts by mass or less, more preferably 55 parts by mass or less, and even more preferably 50 parts by mass or less, based on 100 parts by mass of the base rubber.
[0030] The crosslinking initiator is blended to crosslink the base rubber component. As the crosslinking initiator, an organic peroxide is suitable. Specific examples of the organic peroxide include dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and di-t-butyl peroxide. These organic peroxides may be used alone or in combination of two or more. Among these, dicumyl peroxide is preferably used.
[0031] The content of the crosslinking initiator may be appropriately adjusted depending on the desired hardness of the spherical core. The content of the crosslinking initiator is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.7 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, based on 100 parts by mass of the base rubber.
[0032] When the rubber composition contains only an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms as a co-crosslinking agent, it is preferable that the rubber composition further contains a metal compound. By neutralizing the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms in the rubber composition with a metal compound, substantially the same effect as when a metal salt of an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms is used as a co-crosslinking agent can be obtained. In addition, a metal compound may also be used when an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and its metal salt are used in combination as a co-crosslinking agent.
[0033] The metal compound is not particularly limited as long as it can neutralize the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms in the rubber composition. Examples of the metal compound include metal hydroxides such as magnesium hydroxide, zinc hydroxide, calcium hydroxide, sodium hydroxide, lithium hydroxide, potassium hydroxide, and copper hydroxide; metal oxides such as magnesium oxide, calcium oxide, zinc oxide, and copper oxide; and metal carbonates such as magnesium carbonate, zinc carbonate, calcium carbonate, sodium carbonate, lithium carbonate, and potassium carbonate. The metal compound is preferably a divalent metal compound, and more preferably a zinc compound. The divalent metal compound reacts with the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms to form a metal bridge. These metal compounds may be used alone or in combination of two or more kinds.
[0034] The rubber composition may further contain an organic sulfur compound, but it is also preferable that the rubber composition does not contain an organic sulfur compound. The organic sulfur compound is not particularly limited as long as it is an organic compound having a sulfur atom in the molecule, and examples thereof include organic compounds having a thiol group (-SH) or a polysulfide bond (-SS-, -SSS-, or -SSSS-) having 2 to 4 sulfur groups, or metal salts thereof (-SM, -SMS-, etc., where M is a metal atom). The organic sulfur compounds can be used alone or in combination of two or more kinds.
[0035] Examples of the organic sulfur compounds include thiophenols, thionaphthols, polysulfides, thiurams, thiocarboxylic acids, dithiocarboxylic acids, sulfenamides, dithiocarbamates, thiazoles, etc. As the organic sulfur compounds, diphenyl disulfides (e.g., diphenyl disulfide, bis(pentabromophenyl) disulfide), thiophenols, and thionaphthols (e.g., 2-thionaphthol) can be suitably used.
[0036] The content of the organic sulfur compound may be appropriately adjusted according to the desired resilience performance of the spherical core. The content of the organic sulfur compound is, for example, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less, per 100 parts by mass of the base rubber.
[0037] The rubber composition may further contain a carboxylic acid and / or a metal salt thereof. The carboxylic acid and / or a metal salt thereof is preferably a carboxylic acid having 1 to 30 carbon atoms and / or a salt thereof. The carboxylic acid may be either an aliphatic carboxylic acid (saturated fatty acid, unsaturated fatty acid) or an aromatic carboxylic acid (benzoic acid, etc.). When the carboxylic acid and / or a metal salt thereof is blended, the amount of the carboxylic acid and / or a metal salt thereof is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the base rubber.
[0038] The rubber composition may contain additives such as a filler for adjusting the weight, an antioxidant, a peptizer, and a softener, as required.
[0039] The filler used in the rubber composition is mainly used as a weight adjusting agent for adjusting the weight of the final golf ball product, and may be added as needed. Examples of the filler include inorganic fillers such as barium sulfate, calcium carbonate, magnesium oxide, tungsten powder, and molybdenum powder.
[0040] The rubber composition is obtained by kneading the base rubber, the co-crosslinking agent, the crosslinking initiator, and other components that are mixed as necessary. The kneading method is not particularly limited, and may be performed using a known kneading machine such as a kneading roll, a Banbury mixer, or a kneader.
[0041] The spherical core can be molded, for example, by hot pressing the rubber composition for the core. The hot press molding conditions for the rubber composition for the core may be appropriately set depending on the rubber composition, but it is usually preferable to heat the rubber composition at 130°C to 200°C for 10 to 60 minutes, or to heat the rubber composition at 130°C to 150°C for 20 to 40 minutes, and then heat the rubber composition at 160°C to 180°C for 5 to 15 minutes in two stages.
[0042] The spherical core has a central hardness (H0), a hardness at a point 2.5 mm away from the center of the spherical core in the radial direction (H2.5 ) The hardness (H 5.0 ) at a point 5.0 mm radially from the center of the spherical core 7.5 ) The hardness (H 10 ) at a point 7.5 mm radially from the center of the spherical core 12.5 ) The hardness (H 15 ) at a point 10 mm radially from the center of the spherical core 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15 <Hs satisfy the relationship of H0 < H By the hardness distribution of the spherical core satisfying the above requirements, the deformation of the spherical core during impact occurs smoothly, and the hitting feeling during approach shots becomes good. When the hitting feeling during approach shots is good, it is easy to feel the reaction in the hand during impact, easy to adjust the hitting force, and the controllability of the flight distance in approach shots is improved.
[0043] The spherical core has the center hardness (H0), the hardness (H 2.5 ), the hardness (H 10 ), the hardness (H 12.5 ), and the hardness (H 15 ) in Shore C hardness, and preferably satisfy the relationships of H 2.5 - H0 ≥ 3.0, H 12.5 - H 10 ≥ 3.0, and H 15 - H 12.5 ≥ 3.0. If the hardness differences (H 2.5 - H0), (H 12.5 - H 10 ), and (H 15 - H 12.5 ) are within the above ranges, the deformation amount of the spherical core during approach shots increases, the initial ball speed immediately after impact can be suppressed lower, and the controllability of the flight distance in approach shots is further improved.
[0044] The central hardness (H0) of the spherical core and the hardness (H 2.5 ) and hardness difference (H 2.5 -H0) is preferably 3.0 or more, more preferably 3.3 or more, and even more preferably 3.5 or more, in Shore C hardness, and is preferably 12.0 or less, more preferably 11.0 or less, and even more preferably 10.0 or less.
[0045] The hardness (H 10 ) and the hardness (H 12.5 ) and hardness difference (H 12.5 -H 10 ) is preferably 3.0 or more, more preferably 3.4 or more, and even more preferably 3.8 or more, in Shore C hardness, and is preferably 11.0 or less, more preferably 10.0 or less, and even more preferably 9.0 or less.
[0046] The hardness (H 12.5 ) and the hardness (H 15 ) and hardness difference (H 15 -H 12.5 ) is preferably 3.0 or more, more preferably 3.4 or more, and even more preferably 3.8 or more, in Shore C hardness, and is preferably 10.0 or less, more preferably 9.0 or less, and even more preferably 8.0 or less.
[0047] The spherical core has a hardness (H 5.0 ), the hardness (H 7.5 ) and the hardness (H 10 ) is Shore C hardness, H 7.5 -H 5.0 <3.0, and H 10 -H 7.5 It is preferable to satisfy the relationship of <3.0. 7.5 -H 5.0 ) and hardness difference (H10 -H 7.5 ) within the above range, the deformation energy generated by the impact of an approach shot is easily transmitted to the inside of the spherical core, making it easier for the spherical core to exhibit its characteristics.
[0048] The hardness (H 5.0 ) and the hardness (H 7.5 ) and hardness difference (H 7.5 -H 5.0 ) is preferably 0.2 or more, more preferably 0.3 or more, and even more preferably 0.4 or more, in Shore C hardness, and is preferably less than 3.0, more preferably 2.8 or less, and even more preferably 2.6 or less.
[0049] The hardness (H 7.5 ) and the hardness (H 10 ) and hardness difference (H 10 -H 7.5 ) is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more, in Shore C hardness, and is preferably less than 3.0, more preferably 2.9 or less, and even more preferably 2.8 or less.
[0050] The hardness difference (Hs-H0) between the center hardness (H0) and the surface hardness (Hs) of the spherical core is preferably 20 or more, more preferably 22 or more, and even more preferably 24 or more, in Shore C hardness. If the hardness difference (Hs-H0) is 20 or more, the hitting feeling on a driver shot is good. The hardness difference (Hs-H0) is preferably 40 or less, more preferably 37 or less, and even more preferably 35 or less.
[0051] The spherical core has a center hardness (H0) of preferably 42 or more, more preferably 44 or more, and even more preferably 46 or more, in Shore C hardness, and preferably 70 or less, more preferably 67 or less, and even more preferably 65 or less.
[0052] The spherical core has a surface hardness (Hs) of preferably 70 or more, more preferably 72 or more, and even more preferably 74 or more, in Shore C hardness, and is preferably 90 or less, more preferably 87 or less, and even more preferably 85 or less.
[0053] The diameter of the spherical core is preferably 34.8 mm or more, more preferably 36.8 mm or more, even more preferably 38.0 mm or more, and is preferably 42.2 mm or less, more preferably 41.8 mm or less, even more preferably 41.2 mm or less, and most preferably 40.8 mm or less.
[0054] When the diameter of the spherical core is 34.8 mm to 42.2 mm, the amount of compressive deformation (the amount of shrinkage of the spherical core in the compressive direction) from when an initial load of 98 N is applied to when a final load of 1275 N is applied is preferably 2.0 mm or more, more preferably 2.5 mm or more, even more preferably 3.0 mm or more, and is preferably 5.0 mm or less, more preferably 4.5 mm or less, even more preferably 4.0 mm or less. If the amount of compressive deformation is within the above range, the hitting feeling is better.
[0055] (Middle class) The golf ball of the present invention has an intermediate layer that encases the spherical core.
[0056] The intermediate layer composition constituting the intermediate layer preferably has a slab hardness (Hm) of 50 or more, more preferably 55 or more, and even more preferably 60 or more, in Shore D hardness. If the slab hardness (Hm) is 50 or more, in Shore D hardness, the distance performance during driver shots is good. Furthermore, the slab hardness (Hm) is preferably 74 or less, more preferably 72 or less, and even more preferably 70 or less, in Shore D hardness. When a golf club has a plurality of intermediate layers, the material hardness Hm is the material hardness of the intermediate layer composition constituting the outermost intermediate layer.
[0057] The thickness (Tm) of the intermediate layer is preferably 0.8 mm or more, more preferably 0.9 mm or more, and even more preferably 1.0 mm or more, and is preferably 3.0 mm or less, more preferably 2.6 mm or less, and even more preferably 2.2 mm or less. When there are multiple intermediate layers, the total thickness of all the intermediate layers is defined as the thickness Tm of the intermediate layers.
[0058] (Outermost cover) The golf ball of the present invention has an outermost cover layer located outside the intermediate layer.
[0059] The cover composition constituting the outermost cover layer preferably has a slab hardness (Hc) of 40 or less, more preferably 38 or less, and even more preferably 36 or less, in Shore D hardness. If the slab hardness (Hc) is 40 or less, in Shore D hardness, the shot feeling during approach shots is good. Furthermore, the slab hardness (Hc) is preferably 20 or more, more preferably 22 or more, and even more preferably 24 or more, in Shore D hardness. If the slab hardness (Hc) is 20 or more, the spin rate during driver shots is not too high, and the flight distance performance is good.
[0060] The intermediate layer composition forming the intermediate layer preferably has a slab hardness (Hm) greater than the slab hardness (Hc) of the cover composition forming the outermost cover layer. If the slab hardness (Hm) is greater than the slab hardness (Hc), the controllability of the flight distance on approach shots can be improved, and the spin rate on driver shots can be suppressed.
[0061] The hardness difference (Hm-Hc) between the slab hardness (Hm) and the slab hardness (Hc), in Shore D hardness, is preferably more than 0, more preferably 5 or more, more preferably 10 or more, and is preferably 50 or less, more preferably 48 or less, and even more preferably 46 or less.
[0062] The thickness (Tc) of the outermost cover layer is preferably 0.4 mm or more, more preferably 0.5 mm or more, and even more preferably 0.6 mm or more; and is preferably 1.0 mm or less, more preferably 0.9 mm or less, and even more preferably 0.8 mm or less.
[0063] (Cover composition, intermediate layer composition) The outermost cover layer and the intermediate layer are preferably formed from a resin composition containing a base resin.
[0064] Examples of base resins used in the resin compositions forming the outermost cover layer and the intermediate layer include ionomer resins, urethane resins (thermoplastic polyurethane elastomers, thermosetting polyurethane elastomers), thermoplastic styrene elastomers, thermoplastic polyamide elastomers, and thermoplastic polyester elastomers.
[0065] Examples of the ionomer resin include a binary ionomer resin in which at least a portion of the carboxyl groups in a binary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms are neutralized with a metal ion; a ternary ionomer resin in which at least a portion of the carboxyl groups in a ternary copolymer of an olefin, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and an α,β-unsaturated carboxylic acid ester are neutralized with a metal ion; and a mixture thereof.
[0066] Examples of the binary ionomer resin include Himilan (registered trademark) 1555 (Na), 1557 (Zn), 1605 (Na), 1706 (Zn), 1707 (Na), AM7311 (Mg), AM7329 (Zn), and AM7337 (manufactured by Mitsui Dow Polychemicals); Surlyn (registered trademark) 8945 (Na), 9945 (Zn), 8140 (Na), 8150 (Na), 9120 (Zn), 9150 (Zn), 6910 (Mg), 6120 (Mg), 7930 (Li), 7940 (Li), and AD8546 (Li) (manufactured by DuPont); and Iotek (registered trademark) 8000 (Na), 8030 (Na), 7010 (Zn), and 7030 (Zn) (manufactured by ExxonMobil Chemicals).
[0067] Examples of the ternary ionomer resin include Himilan AM7327(Zn), 1855(Zn), 1856(Na), and AM7331(Na) (manufactured by Mitsui Dow Polychemicals); Surlyn 6320(Mg), 8120(Na), 8320(Na), 9320(Zn), 9320W(Zn), HPF1000(Mg), and HPF2000(Mg) (manufactured by DuPont); and Iotec 7510(Zn), 7520(Zn) (manufactured by ExxonMobil Chemicals). Note that Na, Zn, Li, Mg, and the like written in parentheses after the trade name of the ionomer resin indicate the metal species of these neutralizing metal ions.
[0068] The urethane resin has a urethane bond in its molecule. The urethane bond can be formed by a reaction between a polyol and a polyisocyanate. The polyol, which is a raw material for the urethane bond, has a plurality of hydroxyl groups, and a low molecular weight polyol and a high molecular weight polyol can be used.
[0069] Specific examples of the thermoplastic polyurethane elastomer include Elastollan (registered trademark) NY80A, NY84A, NY88A, NY95A, ET885, and ET890 (manufactured by BASF Japan Ltd.).
[0070] As the thermoplastic styrene-based elastomer, a thermoplastic elastomer containing a styrene block can be preferably used. The styrene block-containing thermoplastic elastomer has a polystyrene block as a hard segment and a soft segment.
[0071] The styrene block-containing thermoplastic elastomer includes styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isoprene-butadiene-styrene block copolymer (SIBS), hydrogenated SBS, hydrogenated SIS, and hydrogenated SIBS. Hydrogenated SBS includes styrene-ethylene-butylene-styrene block copolymer (SEBS). Hydrogenated SIS includes styrene-ethylene-propylene-styrene block copolymer (SEPS). Hydrogenated SIBS includes styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS).
[0072] Examples of the thermoplastic styrene-based elastomer include TEFABLOC T3221C, T3339C, SJ4400N, SJ5400N, SJ6400N, SJ7400N, SJ8400N, SJ9400N, and SR04 (manufactured by Mitsubishi Chemical Corporation).
[0073] The resin composition (cover composition) forming the outermost cover layer preferably contains a urethane resin and / or an ionomer resin as a base resin, and more preferably contains a urethane resin. When the outermost cover layer contains a urethane resin as a base resin, the spin performance of the golf ball is further improved, and the spin amount in approach shots in particular is further improved.
[0074] When the cover composition contains a urethane resin as a base resin, the content of the urethane resin in the base resin is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The cover composition may contain only a urethane resin (preferably a thermoplastic urethane elastomer) as a base resin. When the cover composition contains an ionomer resin as a base resin, the content of the ionomer resin in the base resin is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. When the ionomer resin is contained, it is also preferable to use a thermoplastic styrene elastomer in combination.
[0075] The resin composition forming the intermediate layer (intermediate layer composition) preferably contains an ionomer resin as a base resin. When the intermediate layer composition contains an ionomer resin, the resilience performance of the golf ball is improved, and the resilience performance in driver shots is particularly excellent. The content of the ionomer resin in the base resin of the intermediate layer composition is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. When the ionomer resin is contained, it is also preferable to use a thermoplastic styrene elastomer in combination.
[0076] The resin composition forming the outermost cover layer and the intermediate layer may contain, in addition to the base resin described above, pigment components such as white pigments (e.g., titanium oxide), blue pigments, and red pigments, weight adjusters such as zinc oxide, calcium carbonate, and barium sulfate, dispersants, antioxidants, ultraviolet absorbers, light stabilizers, fluorescent materials, or fluorescent brighteners.
[0077] The content of the white pigment (e.g., titanium oxide) is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, based on 100 parts by mass of the base resin. By making the content of the white pigment 0.5 parts by mass or more, it is possible to impart hiding power to the intermediate layer and the outermost cover layer. In addition, if the content of the white pigment is 10 parts by mass or less, the durability of the obtained intermediate layer and the outermost cover layer is good.
[0078] The method for forming the intermediate layer is not particularly limited, but examples include a method in which the intermediate layer composition is first molded into a hemispherical half shell, two of which are used to encase a spherical core and then pressure molded, or a method in which the intermediate layer composition is directly injection molded onto the spherical core to encase the sphere.
[0079] Methods for molding the cover include, for example, a method in which a hollow shell is molded from the cover composition, and a sphere (a sphere with a spherical core or an intermediate layer) is coated with the multiple shells and compression molded (preferably, a method in which a hollow half shell is molded from the cover composition, and the sphere is coated with two half shells and compression molded), or a method in which the cover composition is directly injection molded onto the sphere.
[0080] The golf ball body with the molded cover is removed from the mold, and is preferably subjected to surface treatment such as deburring, cleaning, and sandblasting, as necessary.
[0081] If desired, a coating film or mark can be formed. The thickness of the coating film is not particularly limited, but is preferably 5 μm or more, more preferably 6 μm or more, even more preferably 7 μm or more, preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. If the thickness is 5 μm or more, the coating film is less likely to wear away even with continuous use, and if the thickness is 50 μm or less, the effect of the dimples can be fully obtained. Note that the coating film is very thin, so it does not impair the effect of the present invention.
[0082] (Golf ball structure) The golf ball of the present invention has a spherical core, an intermediate layer covering the spherical core, and an outermost cover covering the intermediate layer. The structure of the golf ball includes a three-piece golf ball consisting of an intermediate layer covering the spherical core and an outermost cover covering the intermediate layer, and a multi-piece golf ball (four-piece golf ball, five-piece golf ball, etc.) consisting of a single-layer spherical core, two or more intermediate layers covering the spherical core, and an outermost cover covering the intermediate layer.
[0083] The diameter of the golf ball of the present invention is preferably 40 mm to 45 mm. From the viewpoint of satisfying the standards of the United States Golf Association (USGA), the diameter is particularly preferably 42.67 mm or more. From the viewpoint of suppressing air resistance, the diameter is more preferably 44 mm or less, and particularly preferably 42.80 mm or less. In addition, the mass of the golf ball of the present invention is preferably 40 g to 50 g. From the viewpoint of obtaining large inertia, the mass is more preferably 44 g or more, and particularly preferably 45.00 g or more. From the viewpoint of satisfying the standards of the USGA, the mass is particularly preferably 45.93 g or less.
[0084] When the golf ball has a diameter of 40 mm to 45 mm, the amount of compressive deformation (amount of shrinkage in the compressive direction) when a final load of 1275 N is applied from an initial load of 98 N is preferably 2.0 mm or more, more preferably 2.1 mm or more, and even more preferably 2.2 mm or more, and is preferably 3.0 mm or less, more preferably 2.9 mm or less, and even more preferably 2.8 mm or less. If the amount of compressive deformation is within the above range, the shot feeling on a driver shot is good.
[0085] The surface hardness of the golf ball, in Shore D hardness, is preferably at least 45, more preferably at least 48, and even more preferably at least 50, and is preferably at most 65, more preferably at most 63, and even more preferably at most 61. If the surface hardness of the golf ball is within the above range, it will have excellent impact resistance and will be less susceptible to surface scratches.
[0086] An example of a golf ball of the present invention is shown in Figure 1. Figure 1 is a partially cutaway cross-sectional view showing a golf ball 2 according to one embodiment of the present invention. The golf ball 2 has a spherical core 4, an intermediate layer 6 that covers the spherical core 4, and an outermost cover layer 8 that covers the intermediate layer 6. A large number of dimples 10 are formed on the surface of the outermost cover layer 8. The portion of the surface of the golf ball other than the dimples 10 is a land 12. The golf ball 2 has a paint layer and a mark layer on the outside of the outermost cover layer 8, but these layers are not shown in the figure. EXAMPLES
[0087] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the following examples, and all modifications and embodiments that do not deviate from the spirit of the present invention are included within the scope of the present invention.
[0088] [Evaluation method] (1) Compressive deformation amount (mm) A Yamada compression tester "SCH" was used to measure the amount of compressive deformation. In this tester, a golf ball or spherical core is placed on a metal hard plate. A metal cylinder is gradually lowered toward the golf ball or spherical core. The golf ball or spherical core is deformed when sandwiched between the bottom of the cylinder and the hard plate. The distance traveled by the cylinder from when an initial load of 98N is applied to the golf ball or spherical core until a final load of 1275N is applied is measured. The amount of compressive deformation (mm) is this distance traveled. The speed of travel of the cylinder until the initial load is applied is 0.83mm / s. The speed of travel of the cylinder from when the initial load is applied to when the final load is applied is 1.67mm / s.
[0089] (2) Core hardness (Shore C hardness) The hardness measured on the surface of the core was taken as the core surface hardness. The core was cut into a hemisphere, and the hardness was measured at the center of the cut surface and at a specified distance in the radial direction from the center. Each hardness was calculated by measuring the hardness at four points and averaging these values. The hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co., Ltd.). The detector used was "Shore C."
[0090] (3) Slab hardness (Shore D hardness) A sheet with a thickness of about 2 mm was prepared by injection molding using the resin composition and stored at 23° C. for two weeks. The hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co.) in a state where three or more sheets were stacked so as not to be affected by the measurement substrate, etc. The detector used was "Shore D."
[0091] (4) Golf ball surface hardness The hardness of the land portion of the surface of the golf ball was measured and taken as the ball surface hardness. Hardness was measured at four points and calculated by averaging these values. Hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co., Ltd.). The detector used was "Shore D".
[0092] (5) Approach shot test A wedge (Cleveland Golf, "RTX (registered trademark) 3 BLADE", loft angle: 58°) was attached to a Golf Laboratory swing machine. The impact point was set to the face center. The golf ball was hit with a head speed of 16 m / sec, and the ball speed, spin rate, and rolling distance (distance from the landing point to the stopping point) immediately after impact were measured. Measurements were performed 12 times for each golf ball, and the average values were used as the measured values for that golf ball. The ball speed and spin rate were measured by taking continuous photographs of the golf ball immediately after it was hit.
[0093] (6) Shot feeling Twenty golfers used a wedge (Cleveland Golf, "RTX (registered trademark) 3 BLADE", loft angle: 58°) to hit approach shots 20 yards away and rated the feel of the ball on a three-point scale: hard, normal, or soft. Judgment criteria ◎: 16 or more golfers rated the shot feeling as soft Good: 12 or more golfers and 15 or less golfers rated the shot feeling as soft △: 8 or more golfers and 11 or less golfers rated the shot feeling as soft ×: Seven or fewer golfers rated the shot feeling as soft
[0094] [Manufacturing golf balls] (1) Preparation of spherical cores The raw materials were kneaded with a kneading roll so as to obtain the composition shown in Table 1, thereby obtaining a core composition. The core composition shown in Table 1 was hot-pressed in upper and lower molds having hemispherical cavities to obtain a spherical core. An appropriate amount of barium sulfate was added so that the mass of the resulting golf ball would be 45.3 g.
[0095] [Table 1]
[0096] The materials used in Table 1 are as follows: Polybutadiene rubber: JSR Corporation, "BR-730" (high cis polybutadiene rubber, cis-1,4-bond content 95% by mass, 1,2-vinyl bond content 1.3% by mass, Mooney viscosity (ML 1+4 (100℃))55, molecular weight distribution (Mw / Mn)3) Natural rubber: Dau Tieng Rubber Corporation, "CV60" (Mooney viscosity (ML 1+4 (100℃))=60) Zinc diacrylate: Nisshoku Techno Fine Chemical Co., Ltd., "ZN-DA90S" Zinc oxide: "Ginrei R" manufactured by Toho Zinc Co., Ltd. Barium sulfate: Sakai Chemical Industry Co., Ltd., "Barium Sulfate BD" Benzoic acid: Tokyo Chemical Industry Co., Ltd. (purity 98% or more) Bis(pentabromophenyl) disulfide: Kawaguchi Chemical Industry Co., Ltd. Diphenyl disulfide: Sumitomo Seika Chemicals Dicumyl peroxide: NOF Corporation, "Percumyl (registered trademark) D"
[0097] (2) Preparation of Resin Compositions (Composition for Intermediate Layer, Composition for Cover) The raw materials were extruded using a twin-screw kneading extruder so as to obtain the composition shown in Table 2, to prepare a pellet-shaped resin composition.
[0098] [Table 2] Surlyn® 8150: Sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by DuPont Himilan (registered trademark) 1605: Sodium ion-neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) AM7329: Sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) 1555: Sodium ion-neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) 1557: Manufactured by Mitsui Dow Polychemicals, zinc ion neutralized ethylene-methacrylic acid copolymer ionomer resin Tefablock T3221C: Thermoplastic styrene elastomer manufactured by Mitsubishi Chemical Corporation Elastollan (registered trademark) NY80A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY84A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY88A: BASF Japan, thermoplastic polyurethane elastomer Elastollan® NY95A: Manufactured by BASF Japan Ltd., thermoplastic polyurethane elastomer Tinuvin® 770: Manufactured by BASF Japan Ltd., hindered amine light stabilizer Titanium dioxide: Manufactured by Ishihara Sangyo Co., Ltd., A-220
[0099] (3) Formation of the intermediate layer and the cover The resin composition (composition for the intermediate layer) was injection-molded onto a spherical core to obtain a sphere coated with the intermediate layer. The obtained sphere coated with the intermediate layer was put into a final mold having a large number of pimples on the cavity surface. A half shell was obtained from the resin composition (composition for the cover) by a compression molding method. Two half shells were coated on the sphere coated with the intermediate layer put into the final mold, and a golf ball having a large number of dimples with a shape in which the shape of the pimples on the cavity surface was inverted was obtained. The results of evaluating the obtained golf ball are shown in Table 3.
[0100]
Table 3
[0101] Golf balls Nos. 1 to 7 are formed from a rubber composition in which the spherical core contains natural rubber, and the hardness distribution of the spherical core satisfies the relationship of H0 < H 2.5 < H 5.0 < H 7.5 < H 10 < H 12.5 < H 15 < Hs, the central hardness (H0) is 60 or less in Shore C hardness, and the slab hardness of the composition for the intermediate layer is greater than the slab hardness of the composition for the cover. In these golf balls Nos. 1 to 7, the ball speed in the approach shot is suppressed low, the rolling distance is reduced, and the hitting feeling is good. Therefore, these golf balls Nos. 1 to 7 have a good hitting feeling at the time of the approach shot and the controllability is improved.
[0102] Golf balls No. 8 to 10, 12, and 13 are the cases where the spherical core is formed from a rubber composition that does not contain natural rubber. Golf ball No. 11 has a spherical core formed from a rubber composition containing natural rubber, and the hardness distribution of the spherical core satisfies the relationship of H0 < H 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15 <Hs, and the core hardness (H0) is 60 or less in Shore C hardness, but the slab hardness of the intermediate layer composition is smaller than the slab hardness of the cover composition. These golf balls No. 8 to 13 have a large rolling distance in an approach shot and a poor hitting feeling. Therefore, these golf balls No. 8 to 13 have poor controllability in an approach shot.
[0103] (Aspect of the present invention) The present invention (1) has a spherical core, an intermediate layer covering the spherical core, and an outermost layer cover covering the intermediate layer. The spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator. The base rubber contains natural rubber. The core hardness (H0), the hardness (H 2.5 ) at a point 2.5 mm in the radial direction from the center of the spherical core, the hardness (H 5.0 ) at a point 5.0 mm in the radial direction from the center of the spherical core, the hardness (H 7.5 ) at a point 7.5 mm in the radial direction from the center of the spherical core, the hardness (H 10 ) at a point 10 mm in the radial direction from the center of the spherical core, the hardness (H 12.5 ) at a point 12.5 mm in the radial direction from the center of the spherical core, the hardness (H 15 ) at a point 15 mm in the radial direction from the center of the spherical core, and the surface hardness (Hs) satisfy H0 < H 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15Satisfies the relationship of Hs, the core hardness (H0) of the spherical core is 60 or less in Shore C hardness, and the slab hardness of the intermediate layer composition forming the intermediate layer is greater than the slab hardness of the cover composition forming the outermost layer cover. A golf ball characterized by this.
[0104] The present invention (2) is the core hardness (H0), the hardness (H 2.5 ), the hardness (H 10 ), the hardness (H 12.5 ) and the hardness (H 15 ) are in Shore C hardness, H 2.5 -H0≧3.0, H 12.5 -H 10 ≧3.0, and H 15 -H 12.5 ≧3.0. The golf ball according to the present invention (1) satisfying the relationship.
[0105] The present invention (3) is the hardness (H 5.0 ), the hardness (H 7.5 ) and the hardness (H 10 ) are in Shore C hardness, H 7.5 -H 5.0 <3.0, and H 10 -H 7.5 <3.0. The golf ball according to the present invention (1) or (2) satisfying the relationship.
[0106] The present invention (4) is the golf ball according to any one of the present inventions (1) to (3), wherein the hardness difference (Hs-H0) between the core hardness (H0) of the spherical core and the surface hardness (Hs) of the spherical core is 20 or more in Shore C hardness.
[0107] The present invention (5) is the golf ball according to any one of the present inventions (1) to (4), wherein the content of the natural rubber is 20% by mass to 100% by mass in 100% by mass of the base rubber.
[0108] The present invention (6) is the golf ball according to any one of the present inventions (1) to (5), wherein the cover composition forming the outermost cover layer is a resin composition containing a urethane resin as a base resin, and the cover composition forming the outermost cover layer has a slab hardness, in Shore D hardness, of 40 or less.
[0109] The present invention (7) is a golf ball according to any one of the present inventions (1) to (6), wherein the intermediate layer composition forming the intermediate layer is a resin composition containing an ionomer resin as a base resin, and the intermediate layer composition forming the intermediate layer has a slab hardness of 50 or more in Shore D hardness. [Explanation of symbols]
[0110] 2: Golf ball, 4: Spherical core, 6: Intermediate layer, 8: Outermost cover, 10: Dimples, 12: Land
Claims
1. A golf ball has a spherical core, a mid layer encasing the spherical core, and an outermost cover encasing the mid layer, the spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator, The base rubber contains natural rubber, The central hardness (H0) of the spherical core, and the hardness (H 2.5 ), hardness at a radial distance of 5.0 mm from the center of the spherical core (H 5.0 ), hardness at a radial distance of 7.5 mm from the center of the spherical core (H 7.5 ), hardness at a radial distance of 10 mm from the center of the spherical core (H 10 ), hardness at a radial distance of 12.5 mm from the center of the spherical core (H 12.5 ), hardness at a radial distance of 15 mm from the center of the spherical core (H 15 ) and surface hardness (Hs), H0<H 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15 <Hs relationship is satisfied, The spherical core has a center hardness (H0) of 60 or less in Shore C hardness, A golf ball characterized in that the slab hardness of the intermediate layer composition forming the intermediate layer is greater than the slab hardness of the cover composition forming the outermost cover layer.
2. The center hardness (H0), the hardness (H 2.5 ), the hardness (H 10 ), the hardness (H 12.5 ) and the hardness (H 15 ) in Shore C hardness, H 2.5 -H0≧3.0、 H 12.5 -H 10 ≧3.0, and H 15 -H 12.5 2. The golf ball according to claim 1, which satisfies the relationship: ≧3.
0.
3. The hardness (H 5.0 ), the hardness (H 7.5 ) and the hardness (H 10 ) in Shore C hardness, H 7.5 -H 5.0 < 3.0, and H 10 -H 7.5 2. The golf ball according to claim 1, which satisfies the relationship: .times. ...
4. 2. The golf ball according to claim 1, wherein the difference in hardness (Hs-H0) between the center hardness (H0) of the spherical core and the surface hardness (Hs) of the spherical core is 20 or more in Shore C hardness.
5. 2. The golf ball according to claim 1, wherein the content of the natural rubber is 20% by weight to 100% by weight based on 100% by weight of the base rubber.
6. the cover composition forming the outermost cover layer is a resin composition containing a urethane resin as a base resin, 2. The golf ball according to claim 1, wherein the cover composition forming the outermost cover layer has a slab hardness of 40 or less in Shore D hardness.
7. the intermediate layer composition forming the intermediate layer is a resin composition containing an ionomer resin as a base resin, 2. The golf ball according to claim 1, wherein the intermediate layer composition forming the intermediate layer has a slab hardness of 50 or more in Shore D hardness.
Citation Information
Patent Citations
Golf ball for exercise field
JP1985092780A
Golf ball for exercise field
JP1986071069A